2008
DOI: 10.1016/j.brainres.2007.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise produces antidepressant and anxiolytic behavioral effects in mice

Abstract: Reports of beneficial effects of exercise on psychological health in humans are increasingly supported by basic research studies. Exercise is hypothesized to regulate antidepressant-related mechanisms and we therefore characterized the effects of chronic exercise in mouse behavioral paradigms relevant to antidepressant actions. Mice given free access to running wheels showed antidepressant-like behavior in learned helplessness, forced-swim (FST) and tail suspension paradigms. These responses were similar to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
273
4
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(323 citation statements)
references
References 65 publications
25
273
4
3
Order By: Relevance
“…The enhancement effect of physical exercise on hippocampal BDNF expression has been consistently reported in previous studies (36,46,47). Enhanced BDNF expression in the hippocampus via exercise inhibits age-induced deterioration of short-term and spatial working memories (33).…”
Section: Discussionsupporting
confidence: 63%
“…The enhancement effect of physical exercise on hippocampal BDNF expression has been consistently reported in previous studies (36,46,47). Enhanced BDNF expression in the hippocampus via exercise inhibits age-induced deterioration of short-term and spatial working memories (33).…”
Section: Discussionsupporting
confidence: 63%
“…Several environmental factors might have contributed to differences among those studies (e.g., the level of physical activity and housing conditions). Duman et al (2008) speculated that reduced locomotion in the open-field that was possibly related to immediate fatigue after running (see also Fuss et al 2010). This seems unlikely to us, however, as even our HR mice do not run voluntarily on wheels at speeds that exceed their maximal aerobic capacity Rezende et al 2005), nor do they show obvious signs of fatigue during or following wheel running (Meek et al 2009;personal observations).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 86%
“…It has been shown that intense physical activity subsequently alters behavior in the open-field, but the results are inconsistent, ranging from reduced (Duman et al 2008;Fuss et al 2010), unaffected (Leasure and Jones 2008), to increased locomotion (Burghardt et al 2004) in rodents after voluntary wheel running. Several environmental factors might have contributed to differences among those studies (e.g., the level of physical activity and housing conditions).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 99%
“…Interestingly, an interaction of antidepressant treatment effects and elevated expression of neurotrophic factors is not limited to pharmacological manipulation. Voluntary exercise was suggested to have antidepressant properties in animal models (Duman et al 2008) and mood-elevating actions in humans (Babyak et al 2000). A recent microarray study showed that also voluntary exercise up-regulated several neurotrophic factors (Hunsberger et al 2007).…”
Section: Paroxetine-induced Effects On Neurotrophic Factorsmentioning
confidence: 99%